Pemodelan Harga Saham PT. Telekomunikasi Indonesia Tbk Menggunakan Model TSR Linier - Ramadani, Kartika; Wahyuningsih, Sri; Hayati, Memi Nor (Program Studi Statistika FMIPA Universitas Mulawarman, 2022)
The movement of the stock price of PT. Telekomunikasi Indonesia Tbk from time to time is relatively erratic, but in 2020 the movement shows an decreasing trend pattern in January-October and an increasing trend pattern in November-December. There needs a stock price modeling for PT. Telekomunikasi Indonesia Tbk which is useful for investors as a consideration in making decisions to invest. In this study, modeling the stock price of PT. Telekomunikasi Indonesia Tbk uses a Time Series Regression (TSR) Linear model. The results of this study obtained a model for the proportion of data in sample 90, a model for the proportion of data in sample 80, and a model for the proportion of data in sample 70. It was found that the residual value of the TSR linear model the white noise assumption and normally distributed is not valid, so it can be concluded that TSR Linear model has not been able to understand all information on stock price data of PT. Telekomunikasi Indonesia Tbk.